THE INFLUENCE OF MOTIVATION TO AVOID USURY, PRODUCT KNOWLEDGE AND RELIGIOUS ON THE DECISION TO BECOME A CUSTOMER AT BPRS GEBU PRIMA - Siregar, Pani Akhiruddin; Anip, Andi (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to see the significant influence between the motivation to avoid usury, product knowledge and religious on the decision to become a customer at BPRS Gebu Prima. The research approach with quantitative methods is described with a multiple linear regression analysis model. The primary data source was obtained by distributing questionnaires to respondents as a sample of 75 customers. Sampling techniques nonprobability by means of incidental sampling. The results of the study are as follows: (1) The estimation model shows an R2 value of 0,210 which represents the value of the coefficient of determination. This means that 21% of the dependen variable variation is able to be explained by the independen variables in this model. The remaining 79% is explained by other causes that are not included in the model; 2) The regression model on the independen variable simultaneously influence the dependen variable, so that the independen variable regression model can be used to predict the dependen variable; and (3) This research produced an output according to the hypothesis that there is a significant influence between the motivation to avoid usury, product knowledge and religious on the decision to become a customer at BPRS Gebu Prima.